Educación, historia reciente y memoria Investigaciones y aproximaciones metodológicas - Legarralde, Martín Roberto (Ágora, 2022)
Education, Recent History and Memory. Research and Methodological Approaches: Recent Latin American history has been marked by processes of political radicalization, dictatorships, authoritarianism and armed conflicts. Education, pedagogical thinking and educational policies in the region were not immune to these historical conditions. This work studies the intersections between the recent history of education, on the one hand, and memory, on the other, a field which adopted methodological perspectives with specific features. The compiled chapters attempt to answer some key questions for Argentina and Colombia: how to approach the role of pedagogical ideas in the revolutionary projects, in the configuration of schools, in the circulation and confrontation of memories about a traumatic past? What place do educational policies and the commitment of educators occupy in the approach to social and political conflict?